2010
DOI: 10.1016/j.specom.2010.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Non-native speech perception in adverse conditions: A review

Abstract: If listening in adverse conditions is hard, then listening in a foreign language is doubly so: non-native listeners have to cope with both imperfect signals and imperfect knowledge. Comparison of native and non-native listener performance in speech-in-noise tasks helps to clarify the role of prior linguistic experience in speech perception, and, more directly, contributes to an understanding of the problems faced by language learners in everyday listening situations. This article reviews experimental studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
192
6
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(211 citation statements)
references
References 161 publications
(238 reference statements)
11
192
6
2
Order By: Relevance
“…The same pattern appears with Dutch listeners' processing both of [ae] versus [e] (vowels that divide a single Dutch category) and of word-final voicing distinctions (which are neutralized in Dutch); in both cases Dutch listeners perform quite well in a low-level choice task (Broersma, 2005), but fail to distinguish lexical minimal pairs such as cattle-kettle or roberope in cross-modal priming (Broersma & Cutler, 2008, 2011 or in eyetracking (Escudero, Hayes-Harb, & Mitterer, 2008;Weber & Cutler, 2004). In fact one of the most wellknown L2 effects, the disproportionate difficulty of listening to an L2 in a noisy environment, shows the same pattern; a review of four decades of literature on this topic (Lecumberri, Cooke, & Cutler, 2010) motivated the conclusion that noise impinges upon the initial uptake of speech by L1 and L2 listeners to an equivalent degree, but L1 listeners recover better from its effects. We see here a similar pattern in the processing of casual speech phenomena.…”
Section: Discussionmentioning
confidence: 97%
“…The same pattern appears with Dutch listeners' processing both of [ae] versus [e] (vowels that divide a single Dutch category) and of word-final voicing distinctions (which are neutralized in Dutch); in both cases Dutch listeners perform quite well in a low-level choice task (Broersma, 2005), but fail to distinguish lexical minimal pairs such as cattle-kettle or roberope in cross-modal priming (Broersma & Cutler, 2008, 2011 or in eyetracking (Escudero, Hayes-Harb, & Mitterer, 2008;Weber & Cutler, 2004). In fact one of the most wellknown L2 effects, the disproportionate difficulty of listening to an L2 in a noisy environment, shows the same pattern; a review of four decades of literature on this topic (Lecumberri, Cooke, & Cutler, 2010) motivated the conclusion that noise impinges upon the initial uptake of speech by L1 and L2 listeners to an equivalent degree, but L1 listeners recover better from its effects. We see here a similar pattern in the processing of casual speech phenomena.…”
Section: Discussionmentioning
confidence: 97%
“…While the scholarly literature still seems to be divided over the definition of what constitutes a bilingual speaker (see Grosjean 2016), the differentiation between second languages (L2) and foreign languages (FL) seems helpful for the discussion at hand. Although both can refer to languages learned after L1 is fully established, a language learned and spoken in an environment in which it is widely used (e.g., in the case of immigrants) is referred to as L2, while a language learned exclusively in an educational environment (e.g., in the case of languages learned at school) or through the media, is referred to as FL (García Lecumberri et al 2010). Consequently, while for L2 speakers speech perception is mainly conditioned by the quantity of signal, for FL speakers it is conditioned by both its quantity and quality.…”
Section: Accents In Production and Comprehensionmentioning
confidence: 99%
“…Second-language learners were chosen as the target population for their documented difficulty with speech perception in noise (Garcia Lecumberri et al, 2010). In general, studies comparing native and second-language learners suggested that normal hearing and native-like phonological awareness are fundamental for good speech perception in noise (Garcia Lecumberri et al, 2010;Mattys et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In general, studies comparing native and second-language learners suggested that normal hearing and native-like phonological awareness are fundamental for good speech perception in noise (Garcia Lecumberri et al, 2010;Mattys et al, 2012). In other words, perceptual problem that second-language learners experience in noise can be considered primarily due to acoustic-phonetic interference from their native language worsened by masking from noise, which in turn have cumulative detrimental impact on higher-level processes, such as syntax, semantics, and pragmatics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation